Leading names in education: Francisco Giner de los Ríos y la Institución Libre de Enseñanza (Journal of Parents and Teachers, 2012)
This article is based on Francisco Giner’s life and also in what he achieved in his life. It is also about the development of education throughout his life and how different ideologies and conceptions ended up living together in the same place making possible the education that we have today.
Keywords: Great education; life skills; education.; History of education